Kinship of Different Kinds: Horses and People in Iceland - Nash, Catherine (Humanimalia, 2020)
This paper brings together an attentiveness to genealogical imaginaries of human and animal lineage and pedigree as modes of figuring connection and difference and recent approaches to interspecies kinship to explore the kinships of horses and people in Iceland. They include the entanglements of human genealogies, family histories, and horse ancestries; the practice of kinship through horses; and human-horse relationships that are shaped by human understandings of kinship among horses. It explores the possibility of recognising the subtle spatialities of kinship between horses and people and the agency of horses in these proximate and partial connections.